Dark matter hypothesis and new possibilities of the Skyrme-Faddeev chiral model - Rybakov, Yuri P. (Discrete and continuous models and applied computational science, 2025)
New possibilities of the 16-spinor realization of the Skyrme-Faddeev chiral model are discussed. Using gauge invariance principle, it is shown that there exist two independent ways for breaking the isotopic invariance symmetry. The first one concerns the interaction with the electromagnetic field (ordinary photons generated by the electric charge) and the second one includes the interaction with the new vector field (shadow/dark photons generated by the special neutrino charge). The neutrino oscillation phenomenon is explained.